Keterampilan Menggunakan Metode Cerita dalam Pembelajaran Pendidikan Agama Islam di TPQ - Asyruni Runi Multahada (Pusat Penelitian dan Penerbitan Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Islam Negeri Raden Fatah Palembang, 2018)
The story has a tremendous impact on the formation of a child's character, especially if the story delivered can impress on the child. However, to convey interesting and memorable stories to children is not arbitrary. Skills using the story method are important to be mastered by the teacher to teach Islamic Education that is fun and memorable in the soul of the santri (students in Islamic school). There are several things that need to be considered in using story methods, including preparation, storytelling techniques and storytelling skills. Preparations that must be made before delivering the story include choosing the theme of the story, preparing teaching properties, and mastering the contents of the story. Then, the techniques that must be mastered by the teacher in conveying the story consist of opening story techniques, storytelling techniques with properties, techniques for dealing with disturbances in storytelling, and techniques for closing and evaluating stories. Storytelling skills that need to be mastered by teachers include movement, vocal and facial expressions as well as language and communication.